Shear Creep Properties and Creep Model of Gravel Sliding Zone: A Case Study of the Zhoujia Landslide in China - Chen, Shizhuang; Xu, Weiya; Sun, Mengcheng; Yan, Long; Hou, Jing; Wu, Weiwei; Xie, Wei-Chau (Frontiers in Earth Science, 2022)
Creep behavior of landslide sliding zones is closely related to the long-term stability and safety of landslides. In this paper, shear creep tests are carried out on undisturbed samples of the gravel sliding zone in the Zhoujia landslide. Creep properties, such as creep rate and long-term strength, of the sliding zone are studied. The result shows that the sliding zone has typical time-dependent behavior. The relationship between the steady strain rate and shear stress can be described by an exponential equation. The long-term strengths of the sliding zone under different normal stresses are determined by using the isochronous curve cluster method. A nonlinear viscoelastic-plastic creep model is developed based on the Nishihara model. The model is shown to be suitable for describing the accelerated creep deformation of the sliding zone. The results obtained are of practical significance for understanding the deformations of the Zhoujia landslide.